PENGUJIAN HIPOTESIS PECKING ORDER THEORY : MELALUI MODERASI PROFITABILITAS - Astutik, Dwi; Aditya, Galuh (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
Key Problem: Over the past 11 years the invoicing industry has shown a declining contribution to GDP, and moderation testing of profitability is still very limited. Objective: examine and analyze the effect of company size, and asset structure on capital structure based on pecking order theory, either directly or through profitability moderation. Originality: development of the pecking order theory hypothesis with moderation of profitability which throughout the previous research review was still very limited. Method: quantitative design with population in manufacturing industry companies listed on the IDX, as many as 223 companies, based on purposive sampling, obtained 80 companies for a period of 4 years. The analysis technique uses the MRA method. Result: the size of the company is in line with the pecking order theory, which has a negative and significant impact, while the asset structure is positive and significant to the capital structure sourced from debt. Moderation tests show that profitability only moderates the effect of firm size on capital structure. Novelty: the emphasis on the results of testing a high fixed asset structure will increase debt, but the way management views will change when the company's profitability is also high, so it does not reinforce the decision. Future Research Agenda: additional independent variables are needed to strengthen the model, such as ownership structure, board of commissioners, audit committee, and so on. It can be expanded from various points of view of other capital structure theories.